Do regions with entrepreneurial neighbors perform better? A spatial econometric approach for German regions - Katharina Pijnenburg; Konstantin A. Kholodilin (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
We use a neoclassical production function to analyze the effects of knowledge spillovers via entrepreneurship on economic performance of 337 German districts. To take the spatial dependence structure of the data into account, we estimate a spatial Durbin model. We highlight the importance of the choice of the appropriate weight matrix. We find positive knowledge spillover effects via entrepreneurship within a certain region. Between regions, entrepreneurship as a vehicle by which knowledge spills over and contributes to economic performance depends largely on the choice of the weight matrix. We see this as evidence for regionally bounded knowledge spillover effects via entrepreneurship.
Keywords: C21; M13; R11; 330; entrepreneurship capital; regional output; spatial weight matrix